A combined transient photovoltage and impedance spectroscopy approach for a comprehensive study of interlayer degradation in non-fullerene acceptor organic solar cells - Adam Pockett (Nanoscale, 2019)
Organic solar cells utilise thin interlayer materials between the active layer and metal electrodes to improve stability and performance. In this work, we combine transient photovoltage (TPV) and impedance spectroscopy (EIS) measurements to study how degradation affects both the active layer and the interlayer. We show that neither technique alone can provide a complete insight into both of these regions: TPV is more suited to studying degradation of the active layer; EIS clearly identifies the properties of the interlayer. By analysing both of these approaches we are able to assess how different interlayers impact the stability of the active layer, as well as how the interlayers themselves degrade and severely limit device performance. EIS measurements are also able to resolve the impact of the interlayer on series resistance even when it is not apparent from standard current–voltage (JV) measurements. The technique could therefore be valuable for the optimisation of all devices.